2023
DOI: 10.1021/acsagscitech.2c00300
|View full text |Cite
|
Sign up to set email alerts
|

Protection of HSP60 in Myzus persicae Treated with Cry7Ab4 Toxin

Abstract: Heat shock proteins (HSPs) are essential for the survival and development of animals under various stresses. However, little is known about the function of HSPs in insects response to Bacillus thuringiensis (Bt) toxins treatment. Here, we investigated the role of HSP60 in Myzus persicae (M. persicae) treated with an active Cry7Ab4 toxic core. First, we demonstrated the insensitivity of M. persicae to the Cry7Ab4 toxic core through a membrane capsule method. Then, using protein pull-down assay, several putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…It has been previously shown that Bt toxins such as Cry1Cb2, 14 Cry7Ab4, 39 Cry41‐related toxin, 15 Cry64Ba and Cry64Ca 40 could be used for the control of sap‐sucking pests. However, there was no report on Bt toxin that could simultaneously target aboveground and belowground species of pests, as Bt toxin has highly species‐specific activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that Bt toxins such as Cry1Cb2, 14 Cry7Ab4, 39 Cry41‐related toxin, 15 Cry64Ba and Cry64Ca 40 could be used for the control of sap‐sucking pests. However, there was no report on Bt toxin that could simultaneously target aboveground and belowground species of pests, as Bt toxin has highly species‐specific activity.…”
Section: Discussionmentioning
confidence: 99%